Molecular docking studies of phytocompounds of Rheum emodi Wall with proteins responsible for antibiotic resistance in bacterial and fungal pathogens: in silico approach to enhance the bio-availability of antibiotics. Issue 8 (24th May 2022) - Rolta, Rajan; Salaria, Deeksha; Kumar, Vikas; Patel, Chirag N.; Sourirajan, Anuradha; Baumler, David J.; Dev, Kamal
Abstract: Rheum emodi Wall. (Himalayan rhubarb) has many pharmacological activities such as antioxidant, antimicrobial, antiviral, anticancer and wound healing. The present study was aimed to understand if major phytocompounds of Rheum emodi could bind proteins responsible for antibiotic resistance in bacterial and fungal pathogens and enhance the potency of antibiotics. The major phytocompounds of R. emodi (emodin, rhein-13c6 and chrysophenol dimethy ether) were retrieved from the Pubchem and target proteins were retrieved from RCSB protein data bank. The docking study was performed by using AutoDock vina software and Molinspiration, swiss ADME servers were used for the determination of Lipinski rule of 5, drug-likeness prediction respectively, whereas, admetSAR and Protox-II tools were used for toxicity prediction. To study the docking accuracy of protein-ligand complexes, MD simulation for 100 ns was done by using Desmond program version 2.0 (Academic version). Among all the selected phytocompounds, emodin showed the best binding affinity against bacterial (Penicillin binding protein 3, 3VSL and fungal target (cytochrome P450 14 alpha-sterol demethylase 1EA1) with binding energy −8.2 and −8.0 Kcal mol −1 respectively. Similarly, rhein-13C6 showed the best binding affinity against fungal target (n-myristoyl transferase 1IYL) with binding energy −8.0 Kcal mol −1 which is higher than antibacterial and antifungal antibiotics. All the selected phytocompounds also fulfill Lipinski rule, non-carcinogenic and non-cytotoxic in nature. These compounds also showed high LD50 value showing non-toxicity of these phytocompounds. MD simulation studies of phytocompounds (emodin and rhein-13C6) define the stability of protein-ligand complexes with in 100 ns time scale. Communicated by Freddie R. Salsbury